A study about the relationship between sociodemographic characteristics, spirituality, and mental health among emerging adults in metro Manila: findings on higher risk for mental health conditions among LGBTQ+ emerging adults - Wong, Penelope M.; Ong, Jasmine Eve C.; Chua, Jasper S.; See, Annika Shanice C.; Alibudbud, Rowalt (Frontiers in Sociology, 2024)
IntroductionMental health disorders are the third most common disorder in the Philippines, showing a need for further studies in this field among the Filipino population. Several studies have shown that sociodemographic characteristics and spirituality could influence the mental health of individuals, although there are sparse studies in the Philippines.ObjectivesThe present study explored the relationship between sociodemographic characteristics and spirituality to depression, anxiety, and stress among emerging adults in Metro Manila.MethodsThe study gathered data using a self-administered sociodemographic characteristics questionnaire, the Core Dimensional Spirituality Questionnaire (CDSQ), and the Depression, Anxiety, Stress Scale (DASS 21). The data collected was then analyzed through linear regression analysis.ResultsMore than half of the participants had significant scores for anxiety, while two out of five participants had significant scores for depression. Almost one out of five participants had significant scores for stress. Depression scores are positively associated with being LGBTQ+ and belief in God, while they are negatively associated with feelings of security. Similarly, anxiety scores are positively associated with being LGBTQ+. Likewise, stress scores are positively associated with being LGBTQ+ and age, while it is negatively associated with feelings of security.ConclusionThe findings suggest that LGBTQ+ emerging adults and those with older age may need additional focus in mental health programs. Likewise, mental health programs may also enhance their activities to increase an individual’s security.